Evaluation of Permanent Deformation of Palm Oil Mill Sludge Modified Asphalt Binder - Mohamad Azali, Fatin Farhawanie; Mohd Kamaruddin, Nurul Hidayah (Recent Trends in Civil Engineering and Built Environment, 2023)
In order to alleviate waste management difficulties, the use of waste modifier in asphalt modification is being investigated extensively. Palm oil mill sludge (POMS) is a common byproduct of the palm oil industry. The impact of this waste material, on the other hand, remains unknown. The application of POMS in asphalt binder modification was proposed in this study. POMS will be mixed with base binder, penetration grade 60/70, at various percentages (1%, 2%, 3%, 4% and 5%) together with aggregates as per governed by Marshall Mix Design. In order to assess the permanent deformation characteristic of POMS modified asphalt mixture, cyclic loading of 300kPa and testing temperature of 40°C were tested. The permanent deformation characteristics of the POMS modified asphalt mixture were then evaluated using three different studies. Under 40°C temperatures, all samples surpass the modified asphalt mixture requirement. All samples under both temperatures, however, met the dynamic creep modulus standard. According to the results of the test, 3% of POMS had the best effect in terms of permanent deformation under 40°C. It may be inferred that the use of POMS as an asphalt binder modification should be restricted to reduce distress.